Iodine removal in intravenous dual-energy CT-cholangiography: is virtual non-enhanced imaging effective to replace true non-enhanced imaging? - Sommer, Christof-Matthias; Schwarzwälder, Christoph Bernhard; Stiller, Wolfram; Stampfl, Ulrike; Bellemann, Nadine; Holzschuh, Maria; Schmidt, Jan; Weitz, Jürgen; Grenacher, Lars; Kauczor, Hans-Ulrich; Radeleff, Boris (European journal of radiology, 2012)
Purpose: To evaluate whether virtual non-enhanced imaging (VNI) is effective to replace true non-enhanced imaging (TNI) applying iodine removal in intravenous dual-energy CT-cholangiography. Materials and Methods: From April 2009 until February 2010, fifteen potential donors for living-related liver transplantation (mean age 37.6±10.8 years) were included. Potential donors underwent a two-phase CT-examination of the liver. The first phase consisted of a single-energy non-enhanced CT-acquisition that provided TNI. After administration of hepatobiliary contrast agent, the second phase was performed as a dual-energy cholangiographic CT-acquisition. This provided VNI. Objective image quality (attenuation values [bile ducts and liver parenchyma] and contrast-to-noise ratio) and subjective overall image quality (1 - excellent; 5 - non diagnostic) were evaluated. Effective radiation dose was compared. Results: For TNI and VNI, attenuation values for bile ducts were 16.8±11.2HU and 5.5±17.0HU (p<0.05) and for liver parenchyma 55.3±8.4HU and 58.1±10.6HU (n.s.). For TNI and VNI, contrast-to-noise ratio was 2.6±0.6HU and 6.9±2.1HU (p<0.001). For VNI, subjective overall image quality was 1 in ten datasets, 2 in four datasets and 3 in one dataset. Effective radiation dose for the dual-energy cholangiographic CT-acquisition was 3.6±0.9mSv and for two-phase single-energy CT-cholangiography 5.1±1.3mSv (p<0.001). Conclusion: In this study on iodine removal in intravenous dual-energy CT-cholangiography, subjective image quality is equivalent, contrast-to-noise ratio is improved and effective radiation dose is reduced when VNI is performed. The differences between TNI and VNI with respect to attenuation values seem to have limited clinical relevance and therefore we consider VNI as effective to replace TNI.